Morphological support for the phylogenetic positioning of Pentastomida and related fossils - Elaine Christine Costa Eloy; Dalton de Sousa Amorim; Martin Lindsey Christoffersen; Waltécio de Oliveira Almeida (Biotemas, 2008)
Pentastomida is a group of parasites that infects the respiratory tracts of vertebrates. They have a mixture of annelid and arthropod characteristics. For that reason, the phylogenetic relationships of the pentastomids have been controversial in proposals of metazoan phylogeny. Forty-seven characters were selected for the analyses of the taxa Annelida, Arthropoda, Kinorhyncha, Loricifera, Nematoda, Nematomorpha, Onychophora, Pentastomida, Priapulida and Tardigrada. The analyses with PAUP resulted in a single shortest cladogram (length 89, ci 0.78, ri 0.86). Our results indicate that Pentastomida is a transitional group between the Arthropoda and some of the Nemathelminth groups such as Nematoda and Nematomorpha.